Generation of Oxygen Vacancy and OH Radicals: A Comparative Study of Bi2WO6 and Bi2WO6−x Nanoplates. Issue 24 (14th October 2015) - Liu, Yang; Wei, Bo; Xu, Lingling; Gao, Hong; Zhang, Mingyi
Abstract: A comparative study of visible‐light‐responsive Bi2 WO6 and oxygen‐deficient Bi2 WO6− x nanoplates was conducted. The formation of oxygen vacancy resulted in the band gap narrowing of oxygen‐deficient Bi2 WO6− x, through an elevation of both of the conduction and valence band positions. FTIR spectra revealed that much more surface hydroxyl groups have been detected after the etching process. The scavengers tests confirmed the generation of ⋅OH radicals during photochemical reaction for Bi2 WO6− x, whereas no . OH radicals can be detected for pure Bi2 WO6 . The photocatalytic activities of optimized Bi2 WO6− x on the decomposition of Rhodamine B (RhB) was three times as high as that of pure Bi2 WO6 . The improvement of photocatalytic activity on degradation of RhB and phenol can be ascribed to the synergistic effect of oxygen deficiency‐induced band shifts, together with the large quantities of surface hydroxyl groups providing active sites for the generation of OH radicals ( . OH). Abstract : (N)O vacancy : A comparative study of visible‐light‐responsive oxygen‐deficient Bi2 WO6− x nanoplates was conducted. The oxygen vacancies resulted in the band gap narrowing of oxygen‐deficient Bi2 WO6− x . The great improvement of photocatalytic activity on degradation of dyes and phenol can be ascribed to the synergistic effect of oxygen deficiency‐induced band shifts, together with the large quantities of surface hydroxyl groups providing active sites for the generation of OH radicals.